(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2020)
Introduction: Skeletal tuberculosis accounts for 10-35% of Extra-Pulmonary Tuberculosis (EPTB) and 3% of all cases of tuberculosis. Spine is involved in about 50% cases of skeletal tuberculosis. The diagnosis of Spine TB in the developing world until recently has been carried out by clinical presentation and neuro imaging modalities like X-ray/CT/MRI. Until the molecular era, the diagnostic tests at laboratories had mostly remained less contributory with low reliability and accuracy. The objective of the study was to review the spinal cases of TB and present an overview of the different methods of microbiological diagnosis in patients with Spine TB at our center. Methodology: Retrospective study (April 2016 – April 2019) of all consecutive patients suspected with pyogenic or Spine TB was undertaken with relevant clinical details. With the radiological screen the probable TB patients were sampled (tissue, pus, abscess fluids and exudates) and were processed for ZN stain, Culture (conventional), Xpert RIF/MTB assay (at reference lab) and Histopathology. Anti-Tubercular Therapy (ATT) was administered to all definitive cases with or without surgery. Results: A total of 26 patients of Definite TB were identified out of 42 suspected. The mean age was47 years (14-78 range). Fever (n=17) and pain (n=18) were most common symptoms reported by over 80% of the patients. The twenty-six patients characteristically had positive radiological changes in MRI. Lumbar (n=6) and thoracic (n=6) vertebrae were equally involved and over 50% (n=14) had two or more vertebral involvement. All 26 spine samples were negative for Acid Fast Bacilli (AFB) by ZN staining. Individually, the positive detection rate by Xpert MTB/RIF was 88% (n=23), by HPE was 65% (n=17) and by culture was 42% (n= 11) respectively. Xpert MTB/RIF was 82.3% sensitive and 64% specific when compared with Histopathological Evidence (HPE) alone and the sensitivity and specificity rose up 81% on comparing with cross HPE and or culture. Conclusion: Improved case detection of Spine TB was noted by using Xpert MTB/RIF assay at our center. We recommend Xpert MTB/RIF molecular test as the first-line investigation at laboratories for all the suspected cases of Spine TB and for confirmation when the clinical and MRI findings are inconclusive or unavailable. Staining and culture have proved less contributory. Age-old Histopathological evidence may no longer be viewed as a reference standard and needs more evaluation. Small and medium sized hospitals may gradually scale-down the Spine TB processing by AFB stain, and consider establishing on-site molecular infrastructure.